The Effect of Weight Training Exercises on The Explosive Power of The Lemb Muscles of Sakato Pencak Silat Athletes - Putra, Rahma De; Mardela, Romi; Haryanto, Jeki; Putra, Juanda (International Martial Arts and Culture Journal, 2024)
Studi Purpose This research discusses the effect of weight training on the leg muscle power of members of the Solok Regency Pencak Silat Athletes. Method This research used a sample of 20 members of the Solok Regency Pencak Silat Athletes. The aim of this research is to find out what factors can increase the explosive power of leg muscles in members of the Solok Regency Pencak Silat Athletes. The experimental research method is used in this research as a research method that can be used to determine the effect of certain treatments on others under controlled conditions. This research uses a One-Group Pretest-Posttest Design, where a pretest is carried out first, then treatment is given and at the final stage a posttest is carried out. The sample used was 20 members of the Solok Regency Pencak Silat Athletes using an instrument in the form of an observation sheet to measure leg muscle power, the Paired Sample T Test is a data analysis technique used to determine pretest and posttest scores. Results of this research show that Weight Training has proven to have quite a good effect on increasing leg muscle power in members of the Solok Regency Pencak Silat Athletes, with an increase of 6m from before being given treatment which was 41.97m and after being given treatment to 47.97 and proven by a significant value. 0.000 < 0.05.